Hebrew masculinities anew - Creangă, Ovidiu 1976- (Sheffield Sheffield Phoenix Press, 2019)
The study of biblical masculinities is now a clearly recognizable discipline in critical biblical gender studies. This book, the third in a series of SPP volumes that include Men and Masculinity in the Hebrew Bible and Beyond (ed. Ovidiu Creanga, 2010) and Biblical Masculinities Foregrounded (ed. Ovidiu Creanga and Peter-Ben Smit, 2014), takes stock of recent methodological and thematic developments, while introducing fresh new questions, expanding traditional approaches, and adding new texts to the corpus of masculinities in the Hebrew Bible
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Masculinity in the Bible; Men in the Bible; Aufsatzsammlung